The Cute Girl Network - Means, Greg (First Second, 2013)
"Jane's new in town. When she wipes out on her skateboard right in front of Jack's food cart, she finds herself agreeing to go on a date with him. Jane's psyched that her love life is taking a turn for the friskier, but it turns out that Jack has a spotty romantic history, to put it mildly. Cue the Cute Girl Network -- a phone tree information-pooling group of local single women. Poor Jane is about to learn every detail of Jack's past misadventures... whether she wants to or not. Will love prevail? In this graphic novel from Greg Means, Americus author MK Reed, and Joe Flood, the illustrator of Orcs, comes a fast, witty, and sweet romantic comedy that is actually funny, and actually romantic. "--